Protection from COVID-19 with a VSV-based vaccine expressing the spike and nucleocapsid proteins - O’Donnell, Kyle L.; Gourdine, Tylisha; Fletcher, Paige; Clancy, Chad S.; Marzi, Andrea (Frontiers in Immunology, 2022)
Successful vaccine efforts countering the COVID-19 pandemic are centralized around the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S) protein as viral antigen and have greatly reduced the morbidity and mortality associated with COVID-19. Since the start of this pandemic, SARS-CoV-2 has evolved resulting in new variants of concern (VOC) challenging the vaccine-established immunologic memory. We show that vaccination with a vesicular stomatitis virus (VSV)-based vaccine expressing the SARS-CoV-2 S plus the conserved nucleocapsid (N) protein was protective in a hamster challenge model when a single dose was administered 28 or 10 days prior to challenge, respectively. In this study, only intranasal vaccination resulted in protection against challenge with multiple VOC highlighting that the addition of the N protein indeed improved protective efficacy. This data demonstrates the ability of a VSV-based dual-antigen vaccine to reduce viral shedding and protect from disease caused by SARS-CoV-2 VOC.